2008
DOI: 10.1371/journal.ppat.1000083
|View full text |Cite
|
Sign up to set email alerts
|

Key Role of Mfd in the Development of Fluoroquinolone Resistance in Campylobacter jejuni

Abstract: Campylobacter jejuni is a major food-borne pathogen and a common causative agent of human enterocolitis. Fluoroquinolones are a key class of antibiotics prescribed for clinical treatment of enteric infections including campylobacteriosis, but fluoroquinolone-resistant Campylobacter readily emerges under the antibiotic selection pressure. To understand the mechanisms involved in the development of fluoroquinolone-resistant Campylobacter, we compared the gene expression profiles of C. jejuni in the presence and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
95
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(99 citation statements)
references
References 74 publications
(121 reference statements)
1
95
2
1
Order By: Relevance
“…When we compared ciprofloxacin induced gene expression in C. jejuni strain 81-176 with another C. jejuni strain NCTC 11168 (Han et al, 2008), we found that only a set of genes in 81-176 showed a similar response to ciprofloxacin as NCTC 11168 (Table 1). For example, we did not find any response in the transcriptional-repair coupling gene mdf as found in the studies of Han et al (2008).…”
Section: Global Analysis Of Differentially Expressed Genesmentioning
confidence: 99%
See 4 more Smart Citations
“…When we compared ciprofloxacin induced gene expression in C. jejuni strain 81-176 with another C. jejuni strain NCTC 11168 (Han et al, 2008), we found that only a set of genes in 81-176 showed a similar response to ciprofloxacin as NCTC 11168 (Table 1). For example, we did not find any response in the transcriptional-repair coupling gene mdf as found in the studies of Han et al (2008).…”
Section: Global Analysis Of Differentially Expressed Genesmentioning
confidence: 99%
“…These transcriptome studies have shown that responses to ciprofloxacin exposure involve DNA-damage repair mechanisms through the SOS response (Kuzminov, 1999). However, C. jejuni lacks LexA (Han et al, 2008), which is important in SOSmediated DNA repair and thus a typical SOS response system is not functional in C. jejuni. It is not known which molecular mechanisms underlying responses to ciprofloxacin cause direct DNA damage, like DNA breaks and fragmentation.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations